Invasion in breast lesions: the role of the epithelial–stroma barrier. Issue 7 (13th February 2018) - Rakha, Emad A; Miligy, Islam M; Gorringe, Kylie L; Toss, Michael S; Green, Andrew R; Fox, Stephen B; Schmitt, Fernando C; Tan, Puay‐Hoon; Tse, Gary M; Badve, Sunil; Decker, Thomas; Vincent‐Salomon, Anne; et al.
Abstract : Despite the significant biological, behavioural and management differences between ductal carcinoma in situ (DCIS) and invasive carcinoma of the breast, they share many morphological and molecular similarities. Differentiation of these two different lesions in breast pathological diagnosis is based typically on the presence of an intact barrier between the malignant epithelial cells and stroma; namely, the myoepithelial cell (MEC) layer and surrounding basement membrane (BM). Despite being robust diagnostic criteria, the identification of MECs and BM to differentiate in‐situ from invasive carcinoma is not always straightforward. The MEC layer around DCIS may be interrupted and/or show an altered immunoprofile. MECs may be absent in some benign locally infiltrative lesions such as microglandular adenosis and infiltrating epitheliosis, and occasionally in non‐infiltrative conditions such as apocrine lesions, and in these contexts this does not denote malignancy or invasive disease with metastatic potential. MECs may also be absent around some malignant lesions such as some forms of papillary carcinoma, yet these behave in an indolent fashion akin to some DCIS. In Paget's disease, malignant mammary epithelial cells extend anteriorly from the ducts to infiltrate the epidermis of the nipple but do not typically infiltrate through the BM into the dermis. Conversely, BM‐like material can be seen around invasive carcinoma cells and around metastatic tumour cell deposits. Here, we review the role of MECs and BM in breast pathology and highlight potential clinical implications. We advise caution in interpretation of MEC features in breast pathology and mindfulness of the substantive evidence base in the literature associated with behaviour and clinical outcome of lesions classified as benign on conventional morphological examination before changing classification to an invasive lesion on the sole basis of MEC characteristics.